CRYSTALLIZATION AND PRELIMINARY DIFFRACTION DATA OF BOTHROPSTOXIN-I ISOLATED FROM THE VENOM OF BOTHROPS-JARARACUSSU - Arni, R. K.; Ward, R. J.; Cintra, ACO; Giglio, JR (Elsevier B.V., 1995)
The myotoxic Lys-49 phospholipase bothropstoxin I was crystallized, and X-ray diffraction data were collected to 3.5 Angstrom resolution. Preliminary analysis reveals the presence of four molecules in the asymmetric unit.